Kajian Potensi Air Tanah pada Formasi Vulkanik di Kecamatan Prambanan, Kabupaten Klaten, Jawa Tengah : Study of Groundwater Potential in Volcanic Formation in Prambanan District, Klaten Regency, Central Java - Erik Febriarta; Septian Vienastra; Gilang Arya Dipayana; Zulfahmi Sitompul; Ajeng Larasati (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2022)
The presence of groundwater in volcanic rock formations is generally found in aquifer lithology in the form of loose deposits. The groundwater potential can be obtained by using the resistivity data approach. The purpose of this study was to determine the potential of aquifer parameters in volcanic formations on the middle slope of Mount Merapi in Prambanan District, Klaten Regency. The characteristics and thickness of the aquifer lithology can be determined by using the resistivity data approach which is correlated with rock material. Potential groundwater aquifer parameters were obtained from pump test measurements to determine the value of transmitivity (T) and value of permeability (K). The resistivity value is measured with a value range of 3 –75 ohm m which is interpreted by the aquifer lithology of loose material in the form of sand with fine to coarse grain sizes. The average thickness of the aquifer lithology is 80 m with free aquifer properties. Potential aquifer parameters in the form of transmitivity (T) of 330.6 m2/day and the value of permeability (K) of 8.03 m/day with an average aquifer thickness of 10 m. This value belongs to the category of high aquifer productivity potential. Keywords: Aquifers, Discharge, Groundwater, Permeability, Resistivity, Transmissivity Abstrak Keterdapatan air tanah pada formasi vulkanik secara umum terdapat di litologi akuifer berupa endapan lepas-lepas. Potensi air tanah tersebut dapat diperoleh dengan pendekatan data resistivitas. Tujuan dari penelitian ini adalah mengetahu potensi parameter akuifer pada formasi vulkanik di lereng tengah Gunung Merapi di Kecamatan Prambanan, Kabupaten Klaten. Untuk mengetahui karakteristik dan tebal litologi akuifer menggunakan pendekatan data resistivitas yang dikorelasikan dengan material batuan. Potensi parameter akuifer air tanah diperoleh dari pengukuran uji pompa untuk mengetahui Nilai transmisivitas/keterusan (T) dan nilai permeabilitas/kelulusan (K). Nilai resistivitas terukur dengan rentang nilai 35–75 ohm m yang diinterpretasikan dengan litologi akuifer material lepas-lepas berupa pasir dengan ukuran butir halus hingga kasar. Ketebalan rata-rata litologi akuifer sebesar 80 m dengan sifat akuifer bebas. Potensi parameter akuifer berupa nilai transmisivitas/keterusan (T) sebesar 330,6 m2/hari dan nilai permeabilitas/kelulusan (K) sebesar 8,03 m/hari dengan ketebalan akuifer rata-rata 10 m. Nilai tersebut termasuk pada katagori potensi produktivitas akuifer tinggi. Kata kunci: Air tanah, Akuifer, Permeabilitas, Resistivitas, Transmisivitas